(untitled) (The Research of Medical Science Review, 2024)
This study aimed to assess the effects of yeast supplementation as a prebiotic in the diets of small and large ruminants, particularly regarding its influence on feed intake, rumen microbial activity, and overall animal productivity. The study encompassed two types of ruminants: sheep (small ruminants) and cattle (large ruminants), with both control and treatment groups receiving meals supplemented with or without yeast. Health and productivity metrics such as feed conversion ratio, body weight gain, and microbial fermentation in the rumen were examined during 12 weeks. The findings demonstrated that including yeast in the diet resulted in notable enhancements in feed efficiency and elevated microbial populations in the rumen, especially those associated with fiber digestion. Furthermore, animals receiving yeast supplementation demonstrated better weight gain and general health conditions compared to the control group. These findings suggest that yeast is an effective prebiotic in ruminant nutrition, improving digestive function and animal growth. This study holds significant implications for livestock producers aiming to enhance animal health and productivity via dietary modifications.